أثر الامتثال على الحوكمة الشرعية في المصارف الإسلامية: THE IMPACT OF COMPLIANCE ON SHARIA GOVERNANCE IN ISLAMIC BANKS - Saleh Hamd, Nagi Hamd; Lubis, Asmuliadi; Mohd Balwi , Mohd Abd Wahab Fatoni (Online Journal of Islamic Management and Finance (OJIMF), 2023)
The study aims to identify the impact of compliance on Sharia governance in Islamic banks in Libya and Jordan. To achieve the objectives of the study, the research model is designed based on previous studies on the relationship between the research variables. The study sample includes a number of employees of Islamic banks in Libya and Jordan. Based on the quantitative approach in this research, all variables were tested by way of the SPSS application and the AMOS statistical software package. Out of 225 copies, (204) samples were collected from the employees of these banks whereby 21 questionnaires were excluded. The study has reached some findings, the most important of which is that there is a statistically significant effect of compliance on Sharia governance in Islamic banks in Libya and Jordan at a significant level of 0.05. It is also clear that the strength of the correlation is high, indicated by the high level of confidence and the high level of assumption amounting to 0.745. The findings also indicate the positive trend of this relationship, that is, compliance is directly proportional to the Sharia governance of the employees of Islamic banks in Libya and Jordan. The study also suggests some recommendations, the most important of which are: That banks should have a general and clear guide and framework for the principles of Sharia governance, and for compliance with laws and Sharia in addition to clearly defining functions. The study advises Islamic banks to deliberate on compliance by adopting and developing compliance functions and establishing an effective management system to evaluate compliance.